Altering the Surgical Approach of Laparoscopic Cholecystectomy - Ehsan Ullah, Waqas Hussain Qureshi, Hamid Raza Laghari, Muhammad Akram, Sadaf Iqbal, Shafatullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Laparoscopic cholecystectomy (LC) is the standard treatment for gallbladder diseases. However, rare anatomical variations can complicate the procedure, requiring modifications to the surgical approach. Objective: This study aims to assess the impact of such variations on surgical outcomes and evaluate the effectiveness of laparoscopic techniques when faced with these challenges. Methods: This retrospective study was conducted at Irfan General Hospital during June 2022 to June 2023. A total of 15 patients who experienced unexpected anatomical anomalies during their LC procedures were included in the study. Adult patients aged 18–80 years who underwent laparoscopic cholecystectomy for symptomatic gallstones, chronic cholecystitis, or other gallbladder-related disorders were included in the study. Only patients who presented with rare anatomical findings during surgery, which required changes in the planned surgical approach, were included. Results: 40% of patients had an aberrant cystic artery, 20% had duplicated cystic ducts, and 13% had accessory bile ducts. Severe adhesions were encountered in 27% of cases. Preoperative imaging, including ultrasound, CT, and MRCP, failed to detect the majority of these variations, particularly aberrant cystic arteries and severe adhesions. Surgical modifications were required in 20% of cases, leading to conversion to open surgery, primarily due to severe adhesions and duplicated cystic ducts. The average hospital stay was 2.3 days (range: 1–5). Conclusions: It is concluded that rare anatomical variations can significantly alter the course of laparoscopic cholecystectomy. Despite the limitations of preoperative imaging in detecting these variations, laparoscopic techniques were successfully adapted to manage these challenges in most cases. Keywords: Laparoscopic cholecystectomy, severe Adhesion, Open Surgery, Hospital Stay.